The Association of Sentence Imitation with Other Language Domains in Bilingual Children - Grech, Helen (Journal of Child Science, 2022)
The association of sentence imitation with other language domains has been of interest to researchers and clinicians for decades. Sentence imitation taps both working memory and linguistic competence. Working memory refers to the ability to recall and manipulate linguistic information making sentence imitation a clinical marker for language ability. Meanwhile, research on the application of sentence imitation with bilingual language pairs is still emerging. This article reports a study on a large sample of Maltese children brought up in an early bilingual language acquisition context. It analyses correlations between a sentence imitation task, verbal comprehension, narrative (story retelling), phonological awareness, and two measures of a phonology test: percentage consonants correct and the inconsistency score. Data were collected from a total of 241 children, aged 24 to 72 months, who were selected randomly from the public birth register. The subtests administered were part of a test battery, namely, the Maltese–English Speech Assessment (MESA) and the Language Assessment for Maltese Children (LAMC). Correlations were calculated for the sentence imitation scores with specific language subtest scores; significant correlations were identified as well as with chronological age. Regression analysis indicated that the sentence imitation subtest of LAMC is a predictor for verbal comprehension and even stronger predictor for phonological awareness. It was concluded that performance on a sentence imitation task is a valid and reliable indication of Maltese bilingual children's language ability.
Keywords: bilingual; sentence imitation; sentence recall